Enhanced photodegradation toward graphene–based MgFe2O4–TiO2: Investigation and optimization. (1st September 2022) - Viet, Thieu Quang Quoc; Phong, Ha Huu Tan; Thinh, Doan Ba; Giang, Nguyen Thi Huong; Dat, Nguyen Minh; Hai, Nguyen Duy; Phong, Mai Thanh; Hieu, Nguyen Huu
Abstract: In this work, graphene–based MgFe2 O4 –TiO2 (MFO–TiO2 @rGO) nanocomposite was synthesized and conducted an efficient photo–treatment with p–nitrophenol (PNP) as a well–known pollutant in water. The ternary material was characterized by modern analysis methods including Fourier transform infrared spectroscopy, X–ray diffraction, Raman spectroscopy, Transmission electron microscopy, Energy–dispersive X–ray spectroscopy, Selected area electron diffraction, and UV–vis spectroscopy. The simultaneous effects of the volume of H2 O2, catalyst dosage, and pH on the photodegradation of p–nitrophenol were also examined by full factorial experimental design according to Box–Behnken designs. As a result, the characterization has confirmed the uniform bounding of MFO and TiO2 nanosizing from 4 to 6 nm on graphene with a high crystallinity degree. The photocatalysis of this material toward PNP can reach up to ∼99.44% in only 60 min reaction under UV control with 1.12 mL H2 O2 added, 38.15 mg catalyst, and pH 9. Besides, in solar condition (directly under sun), the material also expressed a relatively impressive capability in degrade PNP from water. Furthermore, the ternary nanocomposite can be easily recycled and reused with an inconsiderable change in yield, represented by the elimination yield of recovered MFO–TiO2 @rGO was significantly more than 90% after ten–run cycles. Indeed, the nanocomposite suggests an efficient pathway for treating organic contaminants in wastewater treatment. Highlights: MFO-TiO2 @rGO nanocomposite was prepared by one-pot hydrothermal method. Catalyst dosage, H2 O2, and pH exhibited a vital role in improving the PNP photodegradation. An optimal route for photocatalytic performance of the nanocomposite within the Box–Behnken model design. The photodegradation showed an impressive impact under solar light.